ANALISIS KESULITAN BELAJAR SISWA PADA MATERI SISTEM EKSKRESI MANUSIA - Anggita Simorangkir; Martina Asiati Napitupulu; Tonggo Sinaga (Universitas Negeri Medan, 2020)
This research aims to know the student’s learning difficulty on the material of Human Excretion System from cognitive aspects and indicator aspects and factors causing students learning difficulties on the Human Excretion System on class XI IPA SMA Swasta Teladan Medan Academic Year 2017/2018. The population of this research is all students of class XI IPA which amounts to 118 students. The sample was taken by purposive sampling which amounts to 45 students. The instruments used to obtain data were tested student learning outcomes in the material of the Human Excretion System and learning difficulties questionnaire. The results of the research showed that students were categorized as incomplete. The percentage of student learning difficulties in cognitive aspect for C1, C2, C3, C4, C5, and C6 is 40,11% (medium), 37,82% (low), 41,69% (medium), 53,39% (medium), 49,15% (medium), dan 60,45% (high). The percentage of student learning difficulties based on the learning indicators is mentioned the meaning of the excretion system and its organs in the amount of 37,29% (low), identify the structure and function of the kidney in the amount of 35,59% (low), describe the structure of the nephron and explain the process of human urine formation in the amount of 42,91% (medium), identify the structure and function of the liver in the amount of 42,94% (medium), identify the structure and function of the lung in the amount of 47,46% (medium), identify the structure and function of the skin in the amount of 48,31% (medium), and determine abnormalities or diseases in human excretory organs in the amount of 55,37% (medium). Difficulties in the indicators of structure and function of the kidney and the process of formation of urine are categorized as inhibitory. Indicators of the understanding of the excretion system and its organs, the structure and function of the lung, the structure and function of the liver, abnormalities in the human excretory system, and the learning system in the material of the human excretory system are quite inhibiting categories. While indicators of the structure and function of the skin are categorized as not inhibiting.